Structuration of Environmental Studies by using Multi- report Ontological Graph - Tarasenko, Roman; Shapovalov, Viktor; Usenko, Stanislav; Shapovalov, Yevhenii (My University, 2021)
The usage of information technologies extended, and the capability of software to classify and structure the information becomes increasingly important. The field of ecology and nature management is no exception. So, it seems relevant to find a solution that can simplify the scientific publications data processing.
Keywords: ontological Graph; environmental Studies; structuration; онтологічний граф; екологічні дослідження; структурування; кафедра харчової хімії